Moderate Exercise Suppresses NF-κB Signaling and Activates the SIRT1-AMPK-PGC1α Axis to Attenuate Muscle Loss in Diabetic db/db Mice - Liu, Hung-Wen; Chang, Sue-Joan (Frontiers in Physiology, 2018)
The clear mechanism of moderate exercise training (Ex) in attenuating muscle loss remains elusive in diabetes. We investigated the effects of moderate exercise training on diabetes-induced nuclear factor-κB (NF-κB) activation and mitochondrial dysfunction. Skeletal muscle size and atrophy signaling pathways were examined in type 2 diabetic db/db mice with or without moderate exercise training (5.2m/min, 1h/day, and 5days/week for a total of 8weeks). Exercise training decreased serum leptin, MCP-1, and resistin levels in db/db+Ex mice, but it did not reduce symptoms of insulin resistance including hyperglycemia, hyperinsulinemia, and impaired glucose tolerance. Moderate exercise training prevented the loss of muscle mass of tibialis anterior and gastrocnemius muscles in db/db+Ex mice. The average cross-sectional area of tibialis anterior muscle was increased significantly in db/db+Ex mice compared with untrained mice (830.6 vs.676.5 μm2). Inhibition of MuRF-1 and K48-linked polyubiquitination was observed in db/db+Ex mice. Exercise training reduced activation of IkBa/NF-kB pathway and lowered IL-6, TNF, F4/80(macrophage marker) at mRNA level in db/db+Ex mice compared with untrained mice. Exercise training did not influence FoxO3a phosphorylation and its upstream regulator Akt. Exercise training increased SIRT1 and PGC1a expression and AMPK and mitochondrial complex IV activities and upregulated genes involved in mitochondrial biogenesis/function including Nrf1, Tfam, and mitochondrial complexes I-V. In conclusion, moderate exercise training inhibits NF-kB signaling and activates SIRT1-AMPKa-PGC1a axis, thereby attenuating type 2 diabetes-related muscle atrophy.